Immunoglobulin G3 Antibodies Specific for the 19-Kilodalton Carboxyl-Terminal Fragment of Plasmodium yoelii Merozoite Surface Protein 1 Transfer Protection to Mice Deficient in Fc-γRI Receptors - Vukovic, Peter (American Society for Microbiology, 2000)
Merozoite surface protein 1 (MSP-1(19)) is a leading malaria vaccine candidate. Specific antibodies contribute to immunity; binding to macrophages is believed to represent the main action of malaria antibodies. We show that an MSP-1(19)-specific immunoglobulin G3 (IgG3) monoclonal antibody can passively transfer protection to mice deficient in the α chain of Fc-γRI whose macrophages cannot bind IgG3.